Kinematics Analysis of a Parallel Coordinate Measuring Machine. (18th April 2013) - Chen, Xiulong; Feng, Weiming; Sun, Xianyang; Gao, Qing
A 4-UPS-UPU 5-Degrees of Freedom PCMM(Parallel coordinate measuring machine), which can achieve three translation degrees of freedom and two rotational degrees of freedom, is presented in this paper. The inverse position model of the 4-UPS-UPU PCMM is established. The Jacobian matrix, and the expressions of velocity and acceleration are deduced. Furthermore, a numerical analysis of the inverse solutions of the position, velocity and acceleration are carried out. The results are confirmed by a virtual simulation of the 4-UPS-UPU PCMM prototype. This research has laid a solid foundation for the motion control and movement performance analysis of the 4-UPS-UPU PCMM.